Antecedents and outcomes of telecom reputation in Ghana. (2018) - Anlesinya, Alex; Bukari, Zakari; Bonuedi, Amy Afi; Mickson, Michael K.; Brefo-Manuh, Adwoa Benewaa; Nyanyofio, Gerald Joseph Nii Tetteh
Although reputation management has gained significant research attentions, the success of particular reputation management strategies in one context or industry does not guarantee their applicability in another place due to differences in culture and other context-dependent characteristics. Hence, this study investigated the antecedents and outcomes of telecom reputation in Ghana's telecommunication industry. Survey data from 534 adult mobile phone users were analysed using factor analysis and multiple regressions. Research findings revealed that the antecedents of telecom reputation in the Ghanaian telecommunication industry are: corporate social responsibility (CSR), customer orientation, perceived employer attractiveness, and perceived service quality. The mean ranking further revealed that CSR is the highest contributor while customer orientation is the least in the formation of positive telecom reputation. Moreover, findings showed that customer satisfaction is a major outcome of telecom reputation and its antecedents. The study adds to the literature by developing a model of antecedents and outcomes of telecom reputation in a developing economy, with significant practical implications for telecom reputation management.